Antecedent Direct And Indirect Of Employee Engagement - Hamidah; Muhamad Azis Firdaus; Slamet Sutanto (Fakultas Ekonomi, Universitas Negeri Jakarta, 2019)
This study aims to analyze the direct and indirect effects of antecedent variables on employee engagement. The study involved 272 respondents from two regional companies in the water sector in the Bogor area. The study took place from April 2018 to May 2019. Analysis of the data used Structural Equation Modeling Partial Least Square (SEMPLS) on employee engagement variables as the first endogenous variable, employee job satisfaction as the second endogenous variable and as mediating variables, as well as organizational culture variables and work environment as an exogenous variable. The results showed that the organizational culture variables, directly and indirectly, did not have a significant effect on the endogenous variables of employee engagement. Exogenous variables of the work environment, directly and indirectly, have a positive and significant influence on the employee engagement variable. The implication of the results of this study is that the Regional Water Supply Company (PDAM) in the Bogor region needs to develop its work environment attributes that can improve employee job satisfaction. This needs to be done considering that employee job satisfaction will affect the degree of employee engagement.